Optimizing flower regulation technology for quality harvest in pomegranate - Kumar, R.; Gora, J. S.; Berwal, M. K. (Indian Horticulture, 2025)
Flower regulation is a critical approach in pomegranate cultivation that modifies the natural fruiting cycle, enabling the plant to produce higher yield of quality fruits during desired season with sustainable use of resources. Pomegranate plant bears male, intermediate, and hermaphrodite flowers on both new and old branches, typically across three flowering seasons known as ambe, mrig and hasta bahar. In hot arid climate, however, the plant tends to flowers irregularly across all three bahars, resulting in low yield of inferior quality fruits with non-synchronized maturity, which is commercially disadvantageous. To address this issue, ICAR-CIAH,Bikaner has standardized flower regulation technology specifically for hot arid climate, ensuring a quality harvest.